INFLUENCE OF CONSUMPTION STRUCTURE FOR ENTERPRISE WHILE INTRODUCING ENERGY SAVING MEASURES - A. V. Ershov; V. T Dolgikh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
Development of methods for complex efficiency evaluation of measures on energy saving can be based on usage of single-factor mathematical models for specific consumption of fuel and power resources by output volume. The paper investigates regularities pertaining to formation of resulting energy efficiency of tire production using introduction of energy saving measures  with due account of changes in industrial consumer program on fuel and power resources and power consumption structure.